2021
DOI: 10.1111/jtxs.12642
|View full text |Cite
|
Sign up to set email alerts
|

Children's acceptability profiles for biscuits with different fiber content

Abstract: Due to the widespread rejection by children of products with high‐fiber content, new approaches to meet the dietary recommendations on fiber intake are necessary. To understand which sensory properties influence this rejection, children's acceptability was examined in high‐fiber biscuits and drivers of liking were identified. One hundred and ten Spanish children (6–12 years old) evaluated the overall liking of eight commercial biscuits with variable fiber content and stated their preference. To study the drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…No association between texture and acoustic parameters and the sensory attribute crispiness was detected. This is in disagreement with the results of da Quinta, Alvarez-Sabatel [24], Gouyo, Mestres [27], Salvador, Varela [28]. Their studies have reported that the LDF, NFP, NSP and Smax are positively correlated with the crispness of a product.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…No association between texture and acoustic parameters and the sensory attribute crispiness was detected. This is in disagreement with the results of da Quinta, Alvarez-Sabatel [24], Gouyo, Mestres [27], Salvador, Varela [28]. Their studies have reported that the LDF, NFP, NSP and Smax are positively correlated with the crispness of a product.…”
Section: Discussionmentioning
confidence: 68%
“…Since the parameters LDF, NFP, NSP and Smax are the indicators of the crispness of a product [24,27,28], these results suggest that when the biscuit is made with 100% chickpea flour, its crispness will be significantly higher than when the mixture of the two flours is used. Figure 2 shows force-time and sound-time curves obtained in the texture and acoustic event analysis for each biscuit.…”
Section: Samplementioning
confidence: 96%
See 2 more Smart Citations